The ethical principles and regulatory frameworks that shape the global landscape of artificial intelligence (AI), situating the analysis within the context of leading international efforts to study and govern AI ethics - Putra, Adam Armi; Pambudi, Rillo; Sulistiani, Heni (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The swift evolution of artificial intelligence (AI) has become a central force driving digital transformation across numerous sectors, including finance, healthcare, education, and security. However, this progress also raises profound ethical and regulatory challenges. This study aims to analyze global approaches to AI ethics and governance through a comprehensive review of leading scholarly works. Floridi et al. (2018), through the AI4People initiative, proposed an ethical framework based on five core principles: promoting good, preventing harm, respecting autonomy, ensuring fairness, and maintaining transparency. These principles are designed to ensure that AI development serves the public good while upholding fundamental human values. Similarly, Mittelstadt et al. (2016) explored ethical concerns associated with computational systems, highlighting issues such as bias, discrimination, and lack of transparency in automated decision-making. Their findings suggest that without effective governance mechanisms, AI systems risk reinforcing existing social inequalities. Meanwhile, Cath (2018) approaches the issue from a legal and policy standpoint, identifying obstacles in national and global AI regulation, including differing country policies and the necessity for flexible yet robust legal frameworks. Based on these insights, this paper contends that AI ethics and governance should be viewed as deeply interrelated dimensions. Developing responsible AI requires a synthesis of ethical standards, legal frameworks, and technological innovation aimed at promoting collective well-being. Therefore, international organizations, governments, and academic institutions play a crucial role in establishing consistent global guidelines to ensure that AI advancement aligns with human-centered values.